2007
DOI: 10.1007/s10517-007-0175-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of autologous bone marrow stem cells in the therapy of spinal cord injury patients

Abstract: We studied the safety and efficiency of transplantation of autologous bone marrow cells in complex therapy of patients with spinal cord injury in the late period of the disease. In control group patients, meningomyeloradiculolis was performed, while in the main group surgical treatment was supplemented by transplantation of autologous bone marrow cells. Transplantation of BM stem cells into the cyst cavity and intravenously was well tolerated, did not cause allergic or inflammatory reactions in the early and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 12 publications
2
81
0
3
Order By: Relevance
“…This and the easy access to BMSCs for autotransplantation explains their use in several human treatment studies using a mixture of BMSCs and hematopoietic (mononuclear) cells (Callera et al, 2006;Chernykh et al, 2007;Saito et al, 2008;Yoon et al, 2007). Unfortunately, these reports included small patient cohorts only, used uncharacterized mixtures of bone-marrow cells, and were mostly not controlled.…”
Section: Neural and Glial Restricted Precursors In Combinationmentioning
confidence: 99%
“…This and the easy access to BMSCs for autotransplantation explains their use in several human treatment studies using a mixture of BMSCs and hematopoietic (mononuclear) cells (Callera et al, 2006;Chernykh et al, 2007;Saito et al, 2008;Yoon et al, 2007). Unfortunately, these reports included small patient cohorts only, used uncharacterized mixtures of bone-marrow cells, and were mostly not controlled.…”
Section: Neural and Glial Restricted Precursors In Combinationmentioning
confidence: 99%
“…No serious complications were reported, and 30.4% of patients who received MSCs at acute and subacute stages showed significant improvements in their ASIA scale position (27). Few clinical studies have shown neurological improvements in MSC-treated patients who during the chronic stage of SCI, when the glial scar is already present (28,29,30,31,32). In these studies, MSCs were transplanted directly into the lesion intrathecally, intravenously and intrathecally (simultaneously) at once, and intraarterially.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Тем не менее, в большинстве недавних кли-нических испытаний используются МСК [38][39][40][41]. Так, Chernykh и соавт [38], как и другие исследователи [39][40][41], использовали аутоло-гичные МСК из костного мозга для терапии спинальной травмы.…”
Section: мск для терапии псмтunclassified
“…Так, Chernykh и соавт [38], как и другие исследователи [39][40][41], использовали аутоло-гичные МСК из костного мозга для терапии спинальной травмы. Когда исследователи сравнили клинические результаты с контроль-ной группой, они сообщили об улучшении по-казателей по шкалам ASIA, Barthel и Ashworth у 66% пациентов [38].…”
Section: мск для терапии псмтunclassified